Need to implement the environmental communication mechanisms for sustainable development: a case study - Mohammad, N. (2010)
The term “environmental communication” is very much related to the concept of environmental governance. It is in fact a new idea in the history of the sustainable development on this earth. The scholars of the present age have been focusing the need for the environmental communication for attaining sustainable development. It is based on the good governance mechanisms, environment and human rights issue along with the spirits of the different religions etc. But it faces numerous problems such as the lack of education, insufficient advertisement, attitudes to looking for profits, lack of religious practice including ethics etc. In order to ensure sustainable development for our generation to generation, the environmental communication is very essential. In this regard, some laws in different countries such as the Information Act, the Environmental Court Act along with many international environmental laws such as the Stockholm Conference 1972; the World Charter for Nature; the Basel Convention 1989; the EC Directive on Environmental Information 1991; the Industrial Accidents Convention 1992; the Eco-Labelling Legislation etc; may be discussed. It is based on the access to information, public participation; access to justice as per the Aarhus Convention 1998 which is remarkable for the purposes of sustainable development on this planet, our home. The study urges to the concerned authorities to implement the existing legal foundations on this earth for our own existence and interest. A case study may also be done at the Department of Media and Communication, the University of Malaya, Malaysia based on the primary and secondary sources.